1986
DOI: 10.1111/j.1476-5381.1986.tb10257.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of 5‐HT1A‐ and α2‐receptors in the decreased 5‐hydroxytryptamine release and metabolism in rat suprachiasmatic nucleus after intravenous 8‐hydroxy‐2‐ (n‐dipropylamino) tetralin

Abstract: 1 The 5-hydroxytryptamine1A-receptor agonist 8-hydroxy-2-(n-dipropylamino) tetralin (8-OH-DPAT, 0.1 mg kg-' i.v.) decreased the height of the extracellular 5-hydroxyindoleacetic acid (5-HIAA) oxidation peak recorded in the suprachiasmatic nucleus (SCN) of the anaesthetized rat by use of differential pulse voltammetry. -2 The decrease in extracellular 5-HIAA produced by 8-OH-DPAT could be partially attenuated by prior administration of the non-selective 5-HT receptor antagonist methiothepin (1 mg kg-i.v.). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Results from recent behavioural and in vivo voltammetry studies have indicated that a2-adrenoceptors may be involved in the actions of intravenously or intrathecally administered 8-OH-DPAT and other 5-HT receptor agonists (Marsden & Martin, 1986;Archer et al, 1986). In view of the present findings, it seems likely that some of the actions of 8-OH-DPAT observed in in vivo experiments may have resulted from blockade of X2-adrenoceptors.…”
Section: Discussionmentioning
confidence: 36%
“…Results from recent behavioural and in vivo voltammetry studies have indicated that a2-adrenoceptors may be involved in the actions of intravenously or intrathecally administered 8-OH-DPAT and other 5-HT receptor agonists (Marsden & Martin, 1986;Archer et al, 1986). In view of the present findings, it seems likely that some of the actions of 8-OH-DPAT observed in in vivo experiments may have resulted from blockade of X2-adrenoceptors.…”
Section: Discussionmentioning
confidence: 36%
“…Stimulation of 5-HTlA receptors has also been shown to increase food intake in rats (Dourish et al, 1985). In addition, idazoxan potentiates some of the behavioural effects of 5-HT agonists (Heal et al, 1986;Dickinson et al, 1991) although others, using different test systems, have shown antagonism (Fozard & McDermott, 1985;Marsden & Martin, 1986). It is unlikely that idazoxan interacts directly with 5-HT receptors since in vitro studies have shown that the concentration of idazoxan required to displace [3H]-5-HT from its binding sites in rat cerebral cortex is greater than 5 pM (A.C. Lane; personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…The partial blockade by 8-OH-DPAT may reflect the use of a modest dose. Thus, it has previously been demonstrated that idazoxan completely blocked the effects of 8-OH-DPAT in moderating 5-HT release and metabolism in the suprachiasmatic nucleus (SCN) of the chloral hydrate anaesthetized rat (Marsden & Martin, 1986).…”
Section: Discussionmentioning
confidence: 99%